The role of sexual orientation in differentiating between perceptions of rape myths, gender role stereotypes and social distance: The case of Israel - Shechory-Bitton Mally; Jaeger Lea (Temida, 2020)
The purpose of the current study was to explore the relationships between Israeli gender role stereotypes, rape myths toward male and female victims, and social distance from sex crime victims and sex offenders, according to the observer’s sex and sexual orientation (gay men, lesbian women, and heterosexual men and women). The data was collected during the end of 2016 and included 401 Israeli participants. A multivariate analysis of variance, as well as series of Pearson analyses, were used to examine the differences between groups as well as to examine the correlations between research variables. Results broadly conformed to predictions, with men generally more negative than women. However, people with a same-sex orientation endorse more liberal gender role attitudes than heterosexuals. In addition, overall, participants expressed greater willingness to maintain social contacts with victims than with offenders. Nonetheless, only among heterosexuals significant negative correlations between rape myths and willingness to maintain social contacts with victims were found.